Vaccination with a codon-optimized A27L-containing plasmid decreases virus replication and dissemination after vaccinia virus challenge - Martínez, Osmarie (Vaccine, 2017)
Smallpox is a disease caused by Variola virus (VARV). Although eradicated by WHO in 1980, the threat of using VARV on a bioterror attack has increased. The current smallpox vaccine ACAM2000, which consists of live vaccinia virus (VACV), causes complications in individuals with a compromised immune system or with previously reported skin diseases. Thus, a safer and efficacious vaccine needs to be developed. Previously, we reported that our virus-free DNA vaccine formulation, a pVAX1 plasmid encoding codon-optimized VACV A27L gene (pA27LOPT) with and without Imiquimod adjuvant, stimulates A27L-specific production of IFN-γ and increases humoral immunity 7 days post-vaccination. Here, we investigated the immune response of our novel vaccine by measuring the frequency of splenocytes producing IFN-γ by ELISPOT, the TH1 and TH2 cytokine profiles, and humoral immune responses two weeks post-vaccination, when animals were challenged with VACV. In all assays, the A27-based DNA vaccine conferred protective immune responses. Specifically, two weeks after vaccination, mice were challenged intranasally with vaccinia virus, and viral titers in mouse lungs and ovaries were significantly lower in groups immunized with pA27LOPT and pA27LOPT + Imiquimod. These results demonstrate that our vaccine formulation decreases viral replication and dissemination in a virus-free DNA vaccine platform, and provides an alternative towards a safer an efficacious vaccine.